PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK TEKS CERPEN BALI MODERN PADA SISWA KELAS XI AP 2 SMK PGRI 4 DENPASAR TAHUN PELAJARAN 2018/2019 - Yarsama, Ketut; Wedaningsih, Ni Luh Putu Wahyu (Widyadari: Jurnal Pendidikan, 2019)
This research was motivated by the lack of students? ability in analyzing the intrinsic elements of short story. It is influenced by several things; as the examplemonotonous learning models application such as discourseand rarely discussion.This phenomenon that was motivated this research about the application of cooperative scriptlearning model to enhance the ability in analyzing the intrinsic elements of Balinese modern short story text. The aims of this study were (1) to determine the effectiveness of the application of cooperative script learning model to enhance the ability in analyzing the intrinsic elements of Balinese modern short story texton students class XI AP 2 Vocational High School PGRI 4 Denpasar academic year 2018/2019, (2) to assess the response ofstudents class XI AP 2 Vocational High School PGRI 4 Denpasar academic year 2018/2019 could enhance the ability in analyzing the intrinsic elements of Balinese modern short story text . The theory used in this study, are: (1) literature, (2) literature appreciation, (3) cooperative learningmodel, (4) cooperative learning script, (5) definition of short story, (6) intrinsic elements of short story. Data collection methods used are testing and observationmethods. The results showed that there is an increase in ability to analyze the intrinsic elements of the short story, it can be evidenced from the average value of students in the first cycle is 74.46 increased in the second cycle to 88.44. In addition there is an increase in the student's response following the first cycle that lesson of 70.12 and arise to 85.76 in the second cycle.